Recycled concrete: a review - Martínez-Molina, W.; Torres-Acosta, A. A.; Alonso-Guzmán, E. M.; Chávez-García, H. L.; Hernández-Barrios, H.; Lara-Gómez, C.; Martínez-Alonso, W.; Pérez-Quiroz, J. T.; Bedolla-Arroyo, J. A.; González-Valdéz, F. M. (Revista ALCONPAT, 2015)
The generation of solid residues of hydraulic concrete, also considered waste, is turning into an environmental problem. The construction material primarily manufactured is Portland cement, but one of the main problems is its high manufacturing temperature which generates pollutants. The use of grinded aggregates that come from the demolition of hydraulic concrete is used to generate recycled hydraulic concrete, a material that could lessen costs, decrease pollution and cheapen construction. Nevertheless, the elaboration of recycled concrete faces the search for optimal designs in order to achieve the highest mechanical performance under static and dynamic requests. This work reviews international advancements in this field.Keywords: Recycled concrete, Solid residues, Portland cement, Aggregates.